Study of The Access Performance of Airport Toll Road on Trans Sumatera Toll Road Bakauheni – Terbanggi Besar (Case Study: Intersection of Natar Toll Road) - Rahmadini, Mustika; Purba, Aleksander; Herianto, Dwi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2020)
The construction of the Trans Sumatra Toll Road provides convenience for the public. The distance from the Natar Toll Gate to the intersection of the Lintas Sumatera Road, which is 2,5 km will interfere with toll performance at the peak of holidays if it is not properly regulated. Therefore, it is necessary to do reaserch to determine the performance of toll roads at the Exit of Natar Toll, to know the performance of roads outside the city on Jalan Branti Raya and to find out the performance of signalized intersections at the Natar Toll Exit Intersection. This reaserch use the 2014 Indonesian Road Capacity Guidelines (PKJI) method. The results show that the performance of the toll road at the Natar Toll Exit was still adequate with degree of saturation with direction 1 is 0,09 and direction 2 is 0,13. The performance of roads outside the city on Jalan Branti Raya  was still adequate with degree of saturation with direction 1 is 0,47 and direction 2 is 0,43. The performance of the signalized intersection at the Natar Toll Exit Intersection is almost saturated with the degree of saturation the south approach is 0.67; the east approach is 0.08 and the north approach is 0.82. The queue for the south approach is 30 meters; the east approach is 2 meters and the north approach is 84 meters. The average delay of the intersection is 25 seconds /skr. To improve the performance of the Natar Toll Exit Intersection, it is necessary to rearrange the green time at this intersection.